The Sea Sight of Istanbul: A Description from Rūḥī al- Khālidī’s (1864–1913) Notebook1 - El Ali, Mariam (Keshif, 2023)
The Sea Sight of Istanbul: A Description from Rūḥī al- Khālidī’s (1864–1913) Notebook1